1988
DOI: 10.1007/bf00862585
|View full text |Cite
|
Sign up to set email alerts
|

Kidney function in adults born with unilateral renal agenesis or nephrectomized in childhood

Abstract: We have evaluated the long-term prognosis in an unselected group of adult patients either uni-nephrectomized in childhood because of hydronephrosis or born with unilateral renal agenesis. Thirty-six patients aged 7-47 years were followed for 7-40 years. In 23 control subjects aged 20-47 years the glomerular filtration rate (GFR) and the p-aminohippuric acid clearance (CPAH) did not change significantly with age. In patients with a single kidney the size of that kidney was larger and GFR and CPAH were higher th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
51
0
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(58 citation statements)
references
References 22 publications
6
51
0
1
Order By: Relevance
“…Finally, 6% of children already had CKD stage 3 or higher during follow-up (congenital 4% versus acquired 9%; P=0.05). Other studies that have included solitary functioning kidney patients with a normal renal ultrasound at diagnosis (suggesting absence of ipsilateral CAKUT) report a relatively mild renal outcome (34,40,42,44). Although the exact proportion of individuals with CKD needs to be determined, the increasing number of studies illustrates that a solitary functioning kidney should not be assumed to be harmless.…”
Section: Clinical Outcomementioning
confidence: 99%
“…Finally, 6% of children already had CKD stage 3 or higher during follow-up (congenital 4% versus acquired 9%; P=0.05). Other studies that have included solitary functioning kidney patients with a normal renal ultrasound at diagnosis (suggesting absence of ipsilateral CAKUT) report a relatively mild renal outcome (34,40,42,44). Although the exact proportion of individuals with CKD needs to be determined, the increasing number of studies illustrates that a solitary functioning kidney should not be assumed to be harmless.…”
Section: Clinical Outcomementioning
confidence: 99%
“…This clinical observation has led to a proposal that remnant glomeruli of maturing kidneys are uniquely susceptible to the development of focal glomerular sclerosis. Unequivocal evidence that the young are indeed predisposed to glomerular damage after nephron loss has recently been obtained from the test in humans of renal function after nephrectomy in childhood versus unilateral renal agenesis by Wikstad et al (25), and histologic demonstration in experimental animals by Celsi et al (26) and O'Donnell et al (27). In contrast to the very good prognosis with normal renal function after loss of a kidney from trauma or transplant donation in the adult, the 15 patients with unilateral renal agenesis studied by Wikstad et al (25) showed a decline in inulin clearance rates, and nearly half developed microalbuminuria.…”
mentioning
confidence: 99%
“…Unequivocal evidence that the young are indeed predisposed to glomerular damage after nephron loss has recently been obtained from the test in humans of renal function after nephrectomy in childhood versus unilateral renal agenesis by Wikstad et al (25), and histologic demonstration in experimental animals by Celsi et al (26) and O'Donnell et al (27). In contrast to the very good prognosis with normal renal function after loss of a kidney from trauma or transplant donation in the adult, the 15 patients with unilateral renal agenesis studied by Wikstad et al (25) showed a decline in inulin clearance rates, and nearly half developed microalbuminuria. In light of the above-discussed mechanisms previously tested in a variety of experimental settings, this predisposition of young glomeruli may be attributed to exaggerated hemodynamic abnormality and/or glomerular hypertrophy that follow nephron loss.…”
mentioning
confidence: 99%
“…Bununla birlikte, tek böbrekli hastalarda karşı böbreğin sağlam olduğu durumda kan basıncı ve renal fonksiyonlarının kontrol grubu ile benzer olduğunu gösteren çalışmalar da mevcuttur (20,21) . Bu çalışmada her iki grupta renal fonksiyon bozukluğu saptanmadı.…”
Section: Discussionunclassified